Enhancing IoT security with a DNA-based lightweight cryptography system - Sehrish Aqeel; Adnan Shahid Khan; Irshad Ahmed Abbasi; Fahad Algarni; Daniel Grzonka (Scientific Reports)
Abstract The rapid increase of internet of things (IoT) devices in our daily lives has highlighted the critical need for strong security measures to protect the integrity and confidentiality of IoT communications. This paper presents a novel solution to this growing problem using a secure and lightweight DNA-based encryption method, elliptic curve encryption (ECC), to secure IoT communications. The research explains how DNA-LWCS (DNA-based lightweight cryptography system) utilizes basic encryption methods to secure data transmission against system complexity while maintaining security effectiveness. The security key ensures enough protection for achieving the necessary level of confidentiality. Three fundamental keys are extracted from publicly accessible DNA sequences to start the procedure during its first phase. When employed together with ECC these keys generate a private key during the second stage of development. During the second stage the keys generate a private key based on ECC (elliptic curve cryptography) protocol. The encryption and decryption of IoT device messages requires this private key during the last operational phase. The combination of intuitive DNA sequences together with ECC generates better security and decreases the strain on systems. Practical evaluations demonstrate that the proposed encryption method offers better security and efficiency compared to existing methods while maintaining weightless operational performance. This makes it an ideal solution to secure IoT data exchange. The encryption method we investigated received detailed study which focused on both security and efficiency criteria during our research timeframe. The research demonstrates our security method outperforms other solutions by maintaining low resource requirements. Our proposed DNA-based encryption system shows potential as a suitable security measure for protecting IoT connections through its lightweight design capabilities.